Computational study of aromaticity, 1H NMR spectra and intermolecular interactions of twisted thia-norhexaphyrin and its multiply annulated polypyrrolic derivatives; Physical Chemistry Chemical Physics; Vol. 21, iss. 45 - Baryshnikov G. V. Gleb Vladimirovich; Valiev R. R. Rashid Rinatovich; Li Qizhao; Li Chengjie; Xie Yongshu; Agren H. Hans (2019, 2019)
Title screen